2011
DOI: 10.1093/bmb/ldr001
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes in economic evaluation: who should value health?

Abstract: The valuation of health states is an integral part of economic evaluation studies. The source of these valuations (general public vs. patients) is surrounded by controversy. Health state values generated by the general public are often different compared with those of patients. General public values may not account for adaptation of the patients; patients' values potentially incorporate self-interest. Decisions on the appropriate source of health values ultimately depend on the specific decision-making context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 31 publications
0
67
0
2
Order By: Relevance
“…people with direct personal experience of illness or injury – assign different health state valuations than the general population [7,8]. A literature review by De Wit et al [9] and a meta-analysis by Peeters et al [10] concluded that patients’ valuations of their own (actual) health states tend to be higher than hypothetical valuations of descriptions of the same states by the general population.…”
Section: Introductionmentioning
confidence: 99%
“…people with direct personal experience of illness or injury – assign different health state valuations than the general population [7,8]. A literature review by De Wit et al [9] and a meta-analysis by Peeters et al [10] concluded that patients’ valuations of their own (actual) health states tend to be higher than hypothetical valuations of descriptions of the same states by the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the health economists' perspective uses a societal perspective in which members of the general public generate utilities in the context of decisions about the alternative allocation of resources. Arguments include the fact that it is not patients who bear the costs associated with health-care decisions but rather the general public (86), and that members of the general public are therefore the best judges of health states because they can at least partially act under 'a veil of ignorance', i.e. they are ignorant of their own future health states and needs, and they are blind to their own self-interest (85,87).…”
Section: Figurementioning
confidence: 99%
“…they are ignorant of their own future health states and needs, and they are blind to their own self-interest (85,87). Nevertheless, there are also strong arguments in favour of using a patient perspective in the context of resource allocation, because patients have full knowledge of, and experience with, their health condition (86)(87)(88) and are directly affected by interventions (89). In addition, even when providing members of the general public with as much information as possible, these descriptions of health states remain incomplete (87,90), leaving the general public with a 'lack of scope' (91).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations